Total quality management in higher education institutions: challenges and future directions. (6th May 2010) - Bilen, Canan
Quality management tools and concepts such as total quality management (TQM) were introduced into higher education in late 1980s. Compared to business implementations, the impact of quality management concepts and tools in higher education institutions has not been as significant. Although TQM has been implemented with success in other service sectors, its implementation in higher education has been mostly limited to non-academic, administrative processes. Unlike manufacturing and other service sector implementations of TQM, in higher education institutions, customer-based quality definition has been problematic, limiting its spread and success. This paper discusses the challenges TQM implementations face in higher education and provides directions to overcome these challenges.